IDENTIFICATION OF COMMON FRAGILE SITES IN CHROMOSOMES OF 2 SPECIES OF BAT (CHIROPTERA, MAMMALIA) - Morielleversute, E.; Varellagarcia, M. (Elsevier B.V., 1994)
In the karyotypes of the bat species Molossus ater and M molossus, spontaneous and bromodeoxyuridine (BrdU)- or aphidicolin (APC)-sensitive fragile sites were located. Four chromosome regions harbored APC-sensitive fragile sites: 1q9 and 8q4 in both M ater and M molossus, 3q3 in M ater, and 1p7 in M molossus. The fragile sites in 1q9 and 8q4 were also observed without induction in M molossus. BrdU-sensitive fragile sites were not detected. Despite observations in several other species, the fragile sites detected in Molossus are not coincident with the breakpoints involved in the chromosome rearrangements occurring in the evolution of 7 species of the Molossidae family.
Keywords: FRAGILE SITE; Chromosome; BAT; BROMODEOXYURIDINE INDUCTION; APHIDICOLIN INDUCTION